Skill-biased technological change, unemployment and brain drain - Harald Fadinger; Karin Mayr (FIW - Research Centre International Economics, 2012)
We develop a model of directed technological change, frictional unemployment and migration to examine the effects of a change in skill endowments on wages, employment rates and emigration rates of skilled and unskilled workers. We find that, depending on the elasticity of substitution between skilled and unskilled workers and the elasticity of the matching function, an increase in the skill ratio can reduce the relative unemployment rate of skilled workers and decrease the relative emigration rate of skilled workers (brain drain). We provide empirical estimates and simulations to support our findings and show that effects are empirically relevant and potentially sizeable.
Keywords: F22; J61; J64; O33; 330; Directed Technological Change; Skill Premia; Unemployment; Brain Drain